2014
DOI: 10.1063/1.4883504
|View full text |Cite
|
Sign up to set email alerts
|

Structural heterogeneities at the origin of acoustic and transport anomalies in glycerol glass-former

Abstract: By means of large scale molecular dynamics simulations, we explore mesoscopic properties of prototypical glycerol glass-former above and below the glass transition. The model used, in excellent agreement with various experimental techniques, permits to carefully study the structure and the vibrational dynamics. We find that a medium range order is present in glycerol glass-former and arises from hydrogen bond network extension. The characteristic size of the structural heterogeneities is related to the anomalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
2
4
0
Order By: Relevance
“…In particular, a recent numerical study [14] in dimension d ¼ 2 has shown, quite surprisingly, that the acoustic damping coefficient Γ does not obey the usual Rayleigh law, but that it should scale as Γ ∼ −k dþ1 ln k, with k the wave vector, in the long wavelength limit. The analysis [14] of all currently available experimental and numerical data [7][8][9][10][11][12][13] supports very convincingly the validity of this prediction.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…In particular, a recent numerical study [14] in dimension d ¼ 2 has shown, quite surprisingly, that the acoustic damping coefficient Γ does not obey the usual Rayleigh law, but that it should scale as Γ ∼ −k dþ1 ln k, with k the wave vector, in the long wavelength limit. The analysis [14] of all currently available experimental and numerical data [7][8][9][10][11][12][13] supports very convincingly the validity of this prediction.…”
supporting
confidence: 59%
“…It is only fairly recently, however, that thanks to the work of Monaco and co-workers it has become possible to directly experimentally probe elastic phonon scattering [7][8][9][10]. At the same time, computational advances have also permitted us to access elastic phonon scattering in the relevant frequency range [11][12][13][14]. In particular, a recent numerical study [14] in dimension d ¼ 2 has shown, quite surprisingly, that the acoustic damping coefficient Γ does not obey the usual Rayleigh law, but that it should scale as Γ ∼ −k dþ1 ln k, with k the wave vector, in the long wavelength limit.…”
mentioning
confidence: 99%
“…This surprising finding substantiates the idea that the bonds of solvents could determine the shear modulus on the long-range scale [7,8]. Moreover, these loosely packed solvent-solvent junctions usually lead to additional scattering of transverse phonons in the THz region, which is quite common for various glasses [10,11]. Very recently, Ding et al [12] introduced the concept of "flexibility volume", a volume-scaled vibrational mean square displacement of THz phonons, which can predict the shear modulus of metallic glasses quantitatively.…”
Section: Introductionsupporting
confidence: 76%
“…Its formulation by Schirmacher et al, hampered by the absence of connection between these moduli and the microscopic problem, considers that the elasticity tensor reduces to fluctuating Lamé constants, the correlations of which are assumed to decay exponentially in space. It predicts the damping coefficients Γ L,T to obey the Rayleigh scaling ∼k d+1 (with d being the space dimension and k being the wavevector), while numerical [7][8][9][10] and experimental [11][12][13][14][15][16][17] data support the existence of a regime where attenuation scales as −k d+1 ln k, 10 possibly limited toward low frequencies 18,19 by a crossover to a final Rayleigh regime. Recently, we have been able to derive FE from a small wavevector approximation of the microscopic problem, which yields a complete specification of all the fluctuating elasticity coefficients and captures their long-range correlated nature.…”
Section: Introductionmentioning
confidence: 97%